2008
DOI: 10.1038/ng.257
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation in PNPLA3 confers susceptibility to nonalcoholic fatty liver disease

Abstract: Nonalcoholic fatty liver disease (NAFLD) is a burgeoning health problem of unknown etiology that varies in prevalence among ethnic groups. To identify genetic variants contributing to differences in hepatic fat content, we performed a genome-wide association scan of nonsynonymous sequence variations (n=9,229) in a multiethnic population. An allele in PNPLA3 (rs738409; I148M) was strongly associated with increased hepatic fat levels (P=5.9×10−10) and with hepatic inflammation (P=3.7×10−4). The allele was most c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

142
2,696
22
63

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 2,879 publications
(2,923 citation statements)
references
References 29 publications
142
2,696
22
63
Order By: Relevance
“…For instance, healthy Indian and Asian men are more prone to develop hepatic steatosis and hepatic insulin resistance than other populations because of specific polymorphisms in the insulin-response element for the apolipoprotein C3 gene (Petersen et al, 2006(Petersen et al, , 2010. Confirming the role of the genome in the pathogenesis of NAFLD, another study revealed that Hispanic adults and children are at high risk for the development of NAFLD due to a missense mutation found in the Patatin-like phospholipase domain-containing protein 3 gene (PNPLA3), which is more present in this ethnic group compared to the general population (Romeo et al, 2008). Interestingly, however, patients with variants of the PNPLA3 gene did not develop insulin resistance, suggesting that in this case NAFLD could be dissociated from insulin resistance (Kantartzis et al, 2009).…”
Section: Ectopic Fat Accumulation Promotes Hepatic Insulin Resistancementioning
confidence: 95%
“…For instance, healthy Indian and Asian men are more prone to develop hepatic steatosis and hepatic insulin resistance than other populations because of specific polymorphisms in the insulin-response element for the apolipoprotein C3 gene (Petersen et al, 2006(Petersen et al, , 2010. Confirming the role of the genome in the pathogenesis of NAFLD, another study revealed that Hispanic adults and children are at high risk for the development of NAFLD due to a missense mutation found in the Patatin-like phospholipase domain-containing protein 3 gene (PNPLA3), which is more present in this ethnic group compared to the general population (Romeo et al, 2008). Interestingly, however, patients with variants of the PNPLA3 gene did not develop insulin resistance, suggesting that in this case NAFLD could be dissociated from insulin resistance (Kantartzis et al, 2009).…”
Section: Ectopic Fat Accumulation Promotes Hepatic Insulin Resistancementioning
confidence: 95%
“…All common haplotypes containing the rs738409[G] allele were more common among individuals with cirrhosis than in the control group (Supplementary Table 4). The rare variant rs6006460[T] reported by Romeo et al 4 is also rare in our Mestizo population (minor allele frequency = 0.002), so we had no power to detect an effect of this variant. The minor T allele of rs6006460 was observed in both the cirrhosis and control groups.…”
Section: B R I E F C O M M U N I C a T I O N Smentioning
confidence: 95%
“…Recently, Romeo et al 4 carried out a GWAS of nonsynonymous sequence variations in a population comprising Hispanics, African Americans and European Americans to identify genetic variants contributing to nonalcoholic fatty liver disease. They found strong evidence of association of an allele in PNPLA3 (rs738409: C>G, NP_079501.2:p.I148M) with increased hepatic fat levels (P = 5.9 × 10 −10 ), and the association remained highly signifi cant (P = 7.0 × 10 −14 ) after adjustment for body mass index, diabetes status, ethanol use and genetic ancestry.…”
Section: B R I E F C O M M U N I C a T I O N Smentioning
confidence: 99%
See 1 more Smart Citation
“…Because the frequency of biopsy-proven NASH in Latinos and non-Latino whites was the same (63% versus 62%, no P value), there must be additional risk factors that are more prevalent in Latinos. The authors acknowledged that the PNPLA3 rs738409 polymorphism-more prevalent in Latinos than nonLatino whites 3 -may be such a risk factor but underemphasize its potential importance. Speliotes et al recently showed that the rs738409 G allele showed an independent association with histologic measures of NAFLD but not with metabolic traits.…”
Section: Describing the Role Of Ethnicity In The Progression Of Nafldmentioning
confidence: 99%